Nimotuzumab Combined with Induction Chemotherapy and Concurrent Chemoradiotherapy in Unresectable Locally Advanced Hypopharyngeal Carcinoma: A Single Institution Experience in China - Tian, Xin (Cancer Manag Res, 2020)
OBJECTIVE: To investigate the curative and adverse effects (AEs) of additional use of nimotuzumab combined with induction chemotherapy and concurrent chemoradiotherapy in unresectable locoregionally advanced hypopharyngeal carcinoma. PATIENTS AND METHODS: We retrospectively evaluated 36 patients with stage III or IVA hypopharyngeal carcinoma who received induction chemotherapy followed by concurrent chemoradiotherapy with or without nimotuzumab. The induction chemotherapy included two or three cycles of TPF regimen. The intensity-modulated radiation therapy (IMRT) dose was 70 Gy to the planning target volume. Concurrent with radiotherapy, patients received chemotherapy consisting of cisplatin q3w. Adjuvant chemotherapy consisting of TPF regimen was administered 1 month later after concurrent chemoradiotherapy. Nimotuzumab (200 mg day 1, q3w) was given to patients concurrently with induction chemotherapy and was administered concurrently with IMRT at a weekly dose of 200 mg. RESULTS: After induction chemotherapy, the objective response rate in patients treated with nimotuzumab (group A) versus those treated without nimotuzumab (group B) was 91.7% versus 58.3% (p=0.029). After concurrent chemoradiotherapy, the objective response rate was 95.8% in group A versus 83.3% in group B (p=0.253). The median follow-up was 22.6 months (range 8.9–39.5 months). The 2-year OS rate in group A and group B were 62.5% (95% CI 55–70%) and 51.8% (95% CI 45–59%), respectively, the 2-year OS rate in group A was better than group B, P<0.05. PFS was 23 months (95% CI 19–27) in group A versus 18 months (95% CI 12–22) in group B, PFS was longer in group A than group B, P<0.05. There was no significant difference in AEs between the two groups. CONCLUSION: Additional use of nimotuzumab combined with induction chemotherapy and concurrent chemoradiotherapy in unresectable locoregionally advanced hypopharyngeal carcinoma yielded better short-term efficacy, also may improve overall survival and progression-free survival than patients without using nimotuzumab. The toxicity was tolerable.